Pengaruh Pesan Kampanye #Mandirinzeoperational2030 di Instagram Terhadap Citra Perusahaan Bank Mandiri Mandiri - David Pamungkas; Winda Dwi Astuti Zebua (STIKes Ibnu Sina Ajibarang, 2025)
With the rapid advancement of technology, the world is increasingly shifting toward the digital era, influencing various aspects of life, including the field of Public Relations (PR). Traditional PR activities that previously relied on print media, radio, or television broadcasts are now experiencing a decline in effectiveness. In response to this shift, organizations and companies are transitioning their communication strategies to digital platforms, one of which is through digital campaigns. Digital campaigns have emerged as a modern form of PR activity that leverages the power of social media to reach a wider, interactive, and more segmented audience. The success of a digital campaign is largely determined by the media used. Currently, Instagram stands out as one of the most popular social media platforms, especially among younger generations, due to its ability to present engaging and easily accessible visual content.Bank Mandiri, as one of the largest banks in Indonesia, is taking advantage of this digital trend by launching digital campaigns through its official Instagram account. This strategy aims to strengthen brand image, increase audience engagement, and expand the company’s communication reach. By utilizing interactive features such as Instagram Stories, Reels, and Live, Bank Mandiri is able to establish more effective two-way communication with its audience. This study aims to analyze the effectiveness of Bank Mandiri’s digital campaign on Instagram and its impact on audience perception and engagement. The results of this analysis are expected to contribute to the development of more adaptive digital PR strategies in the current era of digital transformation.